2016
DOI: 10.4236/ce.2016.74065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of School Based Assessment Teacher Training Programme

Abstract: This study employed the Kirkpatrick Evaluation Model to assess the reaction of in-service teacher training program on School Based Assessment (SBA) and its contribution towards teacher's learning (knowledge, skills and attitudes). Kirkpatrick evaluation model has four stages, namely the assessments of reaction, learning (knowledge, skills and attitudes), behavioural and outcomes. This study will discuss the first two stages of assessments that is reaction and learning (knowledge, skills and attitudes). This qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…This shows that the trainers were of a good standard and were chosen well by the training centres. This finding is consistent with the findings of Hassan et al [104] and Yusoff et al [105] in studies that also indicated that trainees were satisfied with the trainers as they assessed their trainers positively.…”
Section: Participantssupporting
confidence: 92%
See 1 more Smart Citation
“…This shows that the trainers were of a good standard and were chosen well by the training centres. This finding is consistent with the findings of Hassan et al [104] and Yusoff et al [105] in studies that also indicated that trainees were satisfied with the trainers as they assessed their trainers positively.…”
Section: Participantssupporting
confidence: 92%
“…Trainees' satisfaction with the training programmes offered to them has also been reported by other studies on training and its evaluation. For example, Chang and Chen [114] and Yusoff et al [105] found that most respondents were satisfied with training delivery and that training programmes were effective.…”
Section: Participantsmentioning
confidence: 99%
“…She found that only reaction and behavior levels of the model correlated moderately and that evaluations conducted at level one do not guarantee the overall success of a training program. Wertz (2005) studied the effectiveness of the CLAD (cross-cultural, language, and academic development) training for a group of K-12 teachers. The data collected from different research tools showed positive responses at levels one, two, and three of the model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study used a four-level evaluation model first recognized in 1959 when Donald L. Kirkpatrick wrote four series of articles entitled "Techniques for Evaluating Training Programs" published in Training and Development, the journal of The American Society for Training and Development (ASTD) [1]. The four-level evaluation method represents a sequence of each stage for evaluating training programs [2].…”
Section: Methodsmentioning
confidence: 99%